(untitled) (Research, Society and Development, 2020)
Civil construction produces several impacts, whether beneficial or not, and may be socioeconomic and environmental. Mitigating measures can be made to alleviate the environmental imbalance, making it necessary to develop materials and techniques to minimize the impacts resulting from these activities. It stands out for soil-cement brick production technologies, not leading to burning in its manufacturing process, in order to ensure sustainable development. The objective of this work is to conduct a survey on the use of soil cement brick in the Metropolitan Region of Cariri, through a questionnaire aimed at professionals working in the area, taking into account their level of commercial knowledge about the use of the product. Data collection was performed online with the submission of a form. Data were collected from 21 professionals, where 71% say they have never used brick in their projects or constructions and only 29% indicate that they have already used the product. The results demonstrated that 71% of the questionnaires answered by companies/professionals in the area of civil construction answered not to use this material. Among the main reasons, they mentioned the difficulty of finding suppliers, the lack of technical knowledge and the non-acceptance of customers. For the 29% who responded to use the product, they report that technological advances in the sector and the need for marketing for the dissemination of the product.